2014
DOI: 10.11648/j.aff.20140302.14
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Zephyr Board Made From Various Rolling Crush Number and Palm Oil Petiole Parts

Abstract: The objective of this research was to evaluate physical and mechanical properties of zephyr board made from palm oil petiole parts. The palm oil petiole parts were distinguished on the basis of rolling crushed number (4, 5 and 6 times,as factor A) and base, middle and upper parts of petiole (factor B). The board was made from three layers of petiole with density of 0.75g.cm⁻ 3 and thickness 1 cm respectively using Phenol formaldehyde (PF) with 12% resin as binding agent and compressed the board at 120ºC temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…MOR of plywood with a veneer of OPT was 30–37 MPa (Mokhtar et al 2011 ). MOR and MOE of zephyr strand board were about 20–39 MPa and 3.0–6.0 GPa, respectively (Wardani et al 2014 ). Lee et al reported that particleboard made with only rubber wood particles has better properties than particleboard made with rubber wood and OPT (Lee et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MOR of plywood with a veneer of OPT was 30–37 MPa (Mokhtar et al 2011 ). MOR and MOE of zephyr strand board were about 20–39 MPa and 3.0–6.0 GPa, respectively (Wardani et al 2014 ). Lee et al reported that particleboard made with only rubber wood particles has better properties than particleboard made with rubber wood and OPT (Lee et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…The obtained wood and bamboo zephyr strands are used to make strand boards (Kim et al 1998 ; Nugroho and Ando 2000 ; Kikata et al 1989a , 1989b ). There are also reports of zephyr strand boards made from oil palm using the zephyr treatment (Wardani et al 2014 ). However, there is no report of using Zephyr treatment for separation.…”
Section: Introductionmentioning
confidence: 99%
“…Palm frond waste which is used as biocomposite is very feasible to be developed so that it can be a solution to replace wood material which is now increasingly scarce. The processing results of this palm waste Zephyr board have a fairly good quality based on testing that can meet the standards of JIS A 5908-20003 Type 18 particle board quality [Wardani, 2014]. [Wardani, 2015], also stated that the quality of Zephyr boards made from waste palm fronds can be compared to other composite boards, the quality of Zephyr boards is better than the quality of plywood made of wood.…”
Section: Floating Architecture/ Floating Buildingsmentioning
confidence: 93%
“…Pelepah sawit sangat baik dimanfaatkan sebagai bahan baku papan zephyr (Wardani, dkk., 2013). Hasil pengujian secara fisis-mekanis papan zephyr dari pelepah sawit cukup baik karena dapat memenuhi standar kualitas papan partikel JIS A 5908-2003 Type 18 (Wardani et al, 2014).…”
Section: Pendahuluanunclassified